2022
DOI: 10.3390/ijms23063074
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Might Regulate Phenotypic Switch of Vascular Smooth Muscle Cells Acting as ceRNA: Implications for In-Stent Restenosis

Abstract: Coronary in-stent restenosis is a late complication of angioplasty. It is a multifactorial process that involves vascular smooth muscle cells (VSMCs), endothelial cells, and inflammatory and genetic factors. In this study, the transcriptomic landscape of VSMCs’ phenotypic switch process was assessed under stimuli resembling stent injury. Co-cultured contractile VSMCs and endothelial cells were exposed to a bare metal stent and platelet-derived growth factor (PDGF-BB) 20 ng/mL. Migratory capacity (wound healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…The significantly differentially expressed lncRNA ACTA2-AS1 has been described so far, mainly in the context of cancer development 26 28 . However, Arencibia et al found that the ACTA2-AS1 might also regulate the phenotypic switch and proliferation of SMCs 29 . In addition, the downregulation of ACTA2-AS1 shows significant enrichment in collagen biosynthesis and alternation in the structure and composition of the extracellular matrix (ECM).…”
Section: Discussionmentioning
confidence: 99%
“…The significantly differentially expressed lncRNA ACTA2-AS1 has been described so far, mainly in the context of cancer development 26 28 . However, Arencibia et al found that the ACTA2-AS1 might also regulate the phenotypic switch and proliferation of SMCs 29 . In addition, the downregulation of ACTA2-AS1 shows significant enrichment in collagen biosynthesis and alternation in the structure and composition of the extracellular matrix (ECM).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have revealed that lncRNAs are aberrantly expressed in breast cancer and closely associated with the development and progression of breast cancer (20). LncRNAs can regulate mRNA expression through multiple mechanisms: epigenetic regulation, transcriptional regulation, post-transcriptional regulation, acting as ceRNA and other molecules mechanisms (21). However, the specific mechanism is still unclear and it is a challenge to use lncRNAs as biomarkers for diagnosis or therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that Hsa_circ_0031608 might be involved in the rupture of intracranial aneurysm via regulating VSMCPS ( Wang et al, 2022 ). Arencibia et al showed that lncRNAs regulate VSMCPS and participate in the pathological process of in-stent stenosis ( Arencibia et al, 2022 ). Additionally, He et al showed that circChordc1 could suppress vascular remodeling and reverse pathological aortic aneurysm progression through optimized VSMCPS and improved their growth ( He et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%